Neuromeric Distribution of Nicotinamide Adenine Dinucleotide Phosphate-Diaphorase Activity in the Adult Lamprey Brain - Pombal, Manuel A.; Megías, Manuel; Lozano, Daniel; López, Jesús M. (Frontiers in Neuroanatomy, 2022)
This study reports for the first time the distribution and morphological characterization of nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d; a reliable marker of nitric oxide synthase activity) positive elements in the central nervous system of the adult river lamprey (Lampetra fluviatilis) on the framework of the neuromeric model and compares their cytoarchitectonic organization with that of gnathostomes. Both NADPH-d exhibiting cells and fibers were observed in all major divisions of the lamprey brain as well as in the spinal cord. In the secondary prosencephalon, NADPH-d positive cells were observed in the mitral cell layer of the olfactory bulb, evaginated pallium, amygdala, dorsal striatum, septum, lateral preoptic nucleus, caudal paraventricular area, posterior entopeduncular nucleus, nucleus of the stria medullaris, hypothalamic periventricular organ and mamillary region sensu lato. In the lamprey diencephalon, NADPH-d labeled cells were observed in several nuclei of the prethalamus, epithalamus, pretectum, and the basal plate. Especially remarkable was the staining observed in the right habenula and several pretectal nuclei. NADPH-d positive cells were also observed in the following mesencephalic areas: optic tectum (two populations), torus semicircularis, nucleus M5 of Schöber, and a ventral tegmental periventricular nucleus. Five different cell populations were observed in the isthmic region, whereas the large sensory dorsal cells, some cells located in the interpeduncular nucleus, the motor nuclei of most cranial nerves, the solitary tract nucleus, some cells of the reticular nuclei, and small cerebrospinal fluid-contacting (CSF-c) cells were the most evident stained cells of the rhombencephalon proper. Finally, several NADPH-d positive cells were observed in the rostral part of the spinal cord, including the large sensory dorsal cells, numerous CSF-c cells, and some dorsal and lateral interneurons. NADPH-d positive fibers were observed in the olfactory pathways (primary olfactory fibers and stria medullaris), the fasciculus retroflexus, and the dorsal column tract. Our results on the distribution of NADPH-d positive elements in the brain of the adult lamprey L. fluviatilis are significantly different from those previously reported in larval lampreys and demonstrated that these animals possess a complex nitrergic system readily comparable to those of other vertebrates, although important specific differences also exist.